2016
DOI: 10.1080/01616412.2016.1243640
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of neuromuscular disorders in Qena governorate/Egypt: population-based survey

Abstract: The overall CPR of neuromuscular disorders in the general population in Qena governorate/Egypt was higher than reported in other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…As depicted in Figure 1, 39 of 9918 identified records were included 13–51 . Studies were conducted in 19 countries between 1958 and 2019.…”
Section: Resultsmentioning
confidence: 99%
“…As depicted in Figure 1, 39 of 9918 identified records were included 13–51 . Studies were conducted in 19 countries between 1958 and 2019.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent in-depth genetic analysis study on a large cohort of FSHD patients, a Lebanese family with five affected individuals was discussed, four of whom were diagnosed with distal 4qA repeat deletions [42]. Literature on FSHD in the Middle East is limited to a few studies from Iran, Egypt and Libya reporting relatively low numbers of patients in NMD cohorts [43][44][45][46]. The molecular diagnosis of FSHD1 remains technically challenging even with NGS, thus explaining in part the low rate of detection of this condition in Middle Eastern populations.…”
Section: Facioscapulohumeral Muscular Dystrophymentioning
confidence: 99%
“…Clinically focused community surveys and hospital studies have offered brief insight into the spectrum of NMDs in the Middle East, including studies in Egypt, Saudi Arabia, and Libya, with sparse reporting on a multitude of NMD subtypes [22,[44][45][46]71]. While large, in-depth, and locus-specific mutational studies are gaining prominence in the region [72,73], extensive studies are needed to address the broad spectrum of genetic NMDs that are rapidly being identified and incorporated into globally recognized patient registries.…”
Section: Comparison With Other Nmd Reportsmentioning
confidence: 99%
“…There is a paucity of data regarding muscle channelopathies in Africa. A population study from Egypt reported a lifetime prevalence of 54 per 100,000 ( 54 , 55 ). A case report documented the first case of an African family (spanning five generations) with hypokalaemic periodic paralysis due to the CACNA1S R1239H variant.…”
Section: Paediatric Nmd In the South African Populationsmentioning
confidence: 99%